Accuracy in dictation after improvement of reading and copying skills in a student with learning difficulties - Verdu, Ana Claudia Moreira Almeida [UNESP]; Oliveira, France Matos De [UNESP] (Programa de pós-gradução em Psicologia, Pontifícia Universidade Católica de Campinas, 2014)
The aim of this study was to use systematic teaching in a clinical setting using software to teach reading and writing in one boy with learning difficulties and obtain accurate performance in dictation. In the pre-test, the student showed good performance in matching-to-sample tasks (96% in matching printed words to dictated words; 88% in matching pictures to dictated words), although he obtained a low percentage of correct answers in the dictation of constructed responses (52%) and manuscripts (24%). The teaching strengthened the selection of printed words matched to dictated words and copying words. The student obtained 100% correct answers in the teaching tasks. In post-tests of dictation, he obtained 100% correct answers in constructed response and 96% correct answers in manuscripts. The results indicate that carefully teaching copying may promote accuracy in the performance of responding to minimal units in dictation tasks.

O objetivo deste trabalho foi adotar, em condições clínicas, um ensino sistemático de leitura e escrita oferecido por um software em um adolescente com características de desempenho condizentes com dificuldades de aprendizagem a fim de que ele obtivesse desempenho preciso em ditado. No pré-teste, o aluno mostrou bom desempenho em relações que envolviam a seleção de palavras impressas diante da palavra ditada (96%) e diante da figura (88%), mas registrou baixa porcentagem de acertos em ditado com construção da resposta (52%) e manuscrito (24%). O ensino fortaleceu a seleção de palavra impressa mediante ditado e cópia da palavra impressa. O aluno obteve 100% de acertos no ensino; nos pós-testes de ditado, obteve 100% de acertos com construção da resposta e 96% de acertos em manuscrito. Os resultados indicam que o ensino criterioso da cópia pode favorecer a precisão no desempenho de responder a unidades mínimas em tarefas de ditado.
Precisão em ditado após fortalecimento de leitura e cópia em um escolar de risco
Keywords: Adolescente; Aprendizagem da escrita; Leitura; Materiais de ensino; Adolescent; Avoidance learning; Reading; Teaching materials